American Studies after Postmodernism - Th. Tsimpouki; K. Blatanis; A. Tseti (Palgrave Macmillan, 2023)
This book explores the major challenges that the long-standing and diversely debated demise of postmodernism signifies for American literature, art, culture, history, and politics, in the present, third decade of the twenty-first century. Its scope comprises a vigorous discussion of all these diverse fields undertaken by distinguished scholars as well as junior researchers, U.S. Americanists and European Americanists alike. Focusing on socio-political and cultural developments in the contemporary U.S., their contributions highlight the interconnectedness of the geopolitical, economic, environmental and technological crises that define the historical present on global scale.